2015
DOI: 10.1080/08974454.2015.1067173
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Care and Trauma in Women Offenders’ Substance Use, Psychiatric Status, and Self-Efficacy Outcomes

Abstract: Using secondary data analysis of 3 separate trauma-informed treatment programs for women offenders, we examine outcomes between those who received both prison and community-based substance abuse treatment (i.e., continuing care; n = 85) and those who received either prison or community aftercare treatment (n = 108). We further account for differences in trauma exposure to examine whether continuing care moderates this effect on substance use, psychiatric severity, and self-efficacy outcomes at follow-up. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 82 publications
4
13
0
Order By: Relevance
“…The intercorrelations among anger, violence, abuse history, mental illness, and substance abuse support prior conclusions that effective programming for women offenders, including those who engage in violence, must address a wide variety of needs rather than just one particular need, such as anger or anger management (Covington, Burke, Keaton, & Norcott, 2008; Gobeil, Blanchette, & Stewart, 2016; Linehan, Bohus, & Lynch, 2007; Palmer et al, 2015; Sacks, 2004; Sacks, McKendrick, & Hamilton, 2012; Saxena, Grella, & Messina, 2016; Saxena, Messina, & Grella, 2014). Yet, a recent review of programs for women in correctional settings revealed that none of them focused heavily on anger, though apart from this review, there are some assessments and descriptions of programs that do attend to women’s anger in a holistic way (Eamon et al, 2002; Fedock, 2015; Kubiak et al, 2014; Tripodi et al, 2011).…”
Section: Discussionsupporting
confidence: 55%
“…The intercorrelations among anger, violence, abuse history, mental illness, and substance abuse support prior conclusions that effective programming for women offenders, including those who engage in violence, must address a wide variety of needs rather than just one particular need, such as anger or anger management (Covington, Burke, Keaton, & Norcott, 2008; Gobeil, Blanchette, & Stewart, 2016; Linehan, Bohus, & Lynch, 2007; Palmer et al, 2015; Sacks, 2004; Sacks, McKendrick, & Hamilton, 2012; Saxena, Grella, & Messina, 2016; Saxena, Messina, & Grella, 2014). Yet, a recent review of programs for women in correctional settings revealed that none of them focused heavily on anger, though apart from this review, there are some assessments and descriptions of programs that do attend to women’s anger in a holistic way (Eamon et al, 2002; Fedock, 2015; Kubiak et al, 2014; Tripodi et al, 2011).…”
Section: Discussionsupporting
confidence: 55%
“…Surgeon General, 2016). Comprehensive programs that would enable women to obtain services and to meet their health and social needs in one location could be valuable in enhancing women’s recovery, which validates previous research findings (Meshberg-Cohen et al, 2016; Saxena et al, 2016).…”
Section: Discussionsupporting
confidence: 85%
“…5859 Accordingly, studies provide evidence of the effectiveness of integrating trauma-informed treatment into women’s addiction treatment, and support the importance of a continuing care model, in which treatment is available both during and after incarceration, for women offenders exposed to traumatic events. 6061 Integrated and ongoing care in turn increases women’s self-efficacy to develop healthier emotional and behavioral responses to adverse events and/or risky situations that they are likely to encounter in the community. 61 …”
Section: Discussionmentioning
confidence: 99%
“…6061 Integrated and ongoing care in turn increases women’s self-efficacy to develop healthier emotional and behavioral responses to adverse events and/or risky situations that they are likely to encounter in the community. 61 …”
Section: Discussionmentioning
confidence: 99%